Observation of Elemental Inhomogeneity and Its Impact on Ionic Conductivity in Li‐Conducting Garnets Prepared with Different Synthesis Methods. Issue 5 (27th March 2021) - Weller, J. Mark; Dopilka, Andrew; Chan, Candace K.
Abstract : Tantalum‐doped lithium lanthanum zirconate garnet (Li7− x La3 Zr2− x Ta x O12 [LLZTO]) has received interest as a solid electrolyte for solid‐state lithium batteries due to its good electrochemical properties and ionic conductivity. However, the source of discrepancies for reported values of ionic conductivity in nominally or nearly equivalent compositions of LLZTO is not completely clear. Herein, synthesis‐related factors that may contribute to the differences in performance of garnet electrolytes are systematically characterized. The conductivity of samples with composition Li6.4 La3 Zr1.4 Ta0.6 O12 prepared by various methods including solid‐state reaction (SSR), combustion, and molten salt synthesis is compared. Varying levels of elemental inhomogeneity, comprising a variation in Ta and Zr content on the level of individual LLZTO particles, are identified. The elemental inhomogeneity is found to be largely preserved even after high‐temperature sintering and correlated with reduced ionic conductivity. It is shown that the various synthesis and processing‐related variables in each of the preparation methods play a role in these compositional variations, and that even LLZTO synthesized via conventional, high‐temperature SSR can exhibit substantial variability in local composition. However, by improving reagent mixing and using LLZTO powder with low agglomeration and small particle size distribution, the compositional uniformity, and hence, ionic conductivity, of sintered garnet electrolytes can be improved. Abstract : Herein, the effect of synthesis method on the ionic conductivity of Li‐ion conducting Li6.4 La3 Zr1.4 Ta0.6 O12 solid‐electrolytes is explored. Elemental inhomogeneity (variation in composition in the solid‐solution Li7− x La3 Zr2− x Ta x O12 ) is observed in powders and sintered electrolytes and is correlated with reduced ionic conductivity. Methods to reduce inhomogeneity are discussed and show that even low‐temperature synthesis can produce electrolytes with high conductivity.